Changes in osteoblast and osteoclast cell count after moringa oleifera leaf extract administration during orthodontic tooth movement - Rika D. Syarif; Tuti Kusumaningsih; Ira Arundina (DiscoverSys Inc., 2020)
Objective: The aim of this study was to analyze the effect of moringa leaf extract administration at 5%, 10%, and 20% concentration toward osteoblast and osteoclast cell count in tension area of Cavia cobaya tooth movement. Matrial and Methods: This study was an experimental research with post test only control group design conducted on Cavia Cobaya. The samples were divided into 4 groups, namely control group (given orthodontic forces), P1 group (given orthodontic forces and Moringa oleifera extract at 5% concentration), P2 group (given orthodontic forces and Moringa oleifera extract at 10% concentration) and P3 group (given orthodontic forces and Moringa oleifera extract at 20% concentration). The samples were sacrificed in day 15 and the tissue were collected for histological examination to examine osteoblast and osteoclast cell count.Results: The Anova test showed a significant difference of osteoblast and osteoclast cell count among groups (p<0.05).Conclusion: Moringa leaves extract administration at 20% concentration for 7 days shows higher number of osteoblast and osteoclast compared to control group, 5% and 10% extract group.